Case Report: Use of Tiao Wei Cheng Qi Decoction to relieve partial intestinal obstruction and enable surgical treatment in primary duodenal adenocarcinoma - Li, Ziyao; Li, Jiahang; Li, Boyang; Sun, Yingying; Wang, Changcheng (Frontiers in Oncology, 2025)
Primary duodenal adenocarcinoma (PDA) is rare and highly invasive malignancies. The onset of the disease is insidious. Patients are often diagnosed when digestive obstruction occurred, leading to poor nutritional status and reduced tolerance for surgical trauma. Additionally, patients commonly experience fluid depletion and gastric drying, which is recognized as a pattern of gastric dryness and fluid injury. This article presents a successful case treated with the modified Decoction for Regulating the Stomach and Resolving Phlegm Formula combined with partial duodenectomy, summarizes both Chinese and Western medical diagnostic and treatment strategies for this disease, and provides valuable clinical experience in treating it.